PERUBAHAN STRUKTUR KEPEMILIKAN AKIBAT AKUISISI DAN PENGARUHNYA TERHADAP KEBIJAKAN DIVIDEN DAN STRUKTUR MODAL - Evi Nopela; M. Masrukhan (Cahaya Ilmu Bangsa, 2024)
This study discusses the changes in ownership structure and aims to examine how these changes affect dividend policy and whether they also impact the capital structure of the company. Changes in ownership structure and capital structure are important topics in the business world. In companies, acquisitions often lead to significant changes in corporate control, share ownership, and future strategies. This research aims to analyze and understand the implications of changes in ownership structure, acquisitions, and how these affect dividend policies and capital structure in terms of managerial, operational, and financial aspects of the company. Changes in ownership structure often influence strategic decision-making patterns, which can lead to significant changes in company policies. This study shows that changes in ownership structure following an acquisition have an impact on dividend policies and also affect the company’s capital structure. Although acquisitions can help companies collaborate and improve, changes in ownership structure must be made carefully to avoid negative long-term consequences for the company.